Anthropological Research on the technique of egg donation in Greece: cultural conceptualizations, social practices, legislative provisions - Τουντασάκη (Eirini Tountasaki) Ειρήνη (Bioethica, 2017)
Legislative provisions regarding the use of reproductive technologies prove the attempt of law to respond to the new social needs and to supply answers to acute ethical and legal dilemmas which have arisen as a result of the dramatic progress of biotechnologies. Nevertheless, legislation must not appear as a simple list of rules. It reflects sociocultural conceptions and reconfigurations which characterize particular historical and political situations while at the same time affect and contribute to the shaping of the social agents choices. I attempt to analyze this interaction between legislative provisions and social practices through the case of legislation of the egg donation technique. Drawing from the combination of the study of laws with the analysis of the anthropological research data -which reproduce the agents discourse- I try to show that legislation does not only defend but also reinforce the infertile couples attempt to normalize the oddity of medically assisted reproduction, to naturalize the birth of a child. The anonymity between all involved parties, the secrecy surrounding the whole process of the use of the egg donors and the construction of similarities between the child and the candidate parents not only meet the regulatory requirements of the legislative provisions but at the same time constitute strategies activated by the agents in order for the donor to be eliminated, the use of foreign eggs to be naturalized, the technique of assisted reproduction to imitate natural reproduction.